GE_GERICHTE C/22123/2010 vom 15. Oktober 2013 - GE Cour de justice (2013)
DIVORCE; ENFANT; OBLIGATION D'ENTRETIEN; LIQUIDATION DU RÉGIME MATRIMONIAL; PRÉVOYANCE PROFESSIONNELLE | CC.285; CC.286; CC.197